Strategi Promosi Jasa dalam Meningkatkan Efektivitas Komunikasi Pemasaran di Era Digital - Sinarwaty Sinarwaty; Indah Sriwana Nurdin; Anggelina Mallisa (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This article analyzes service promotion strategies in improving the effectiveness of marketing communication in the digital era. The study applies a descriptive qualitative approach with a literature review method. The main reference is Fatihudin and Firmansyah (2019) in Pemasaran Jasa: Strategi, Mengukur Kepuasan, dan Loyalitas Pelanggan. The analysis is strengthened by journal articles that discuss integrated marketing communication, website quality, electronic word of mouth, customer trust, satisfaction, and loyalty. The findings show that service promotion requires a more complex approach than the promotion of tangible goods because services are intangible, difficult to evaluate before consumption, and strongly influenced by the quality of interaction between providers and customers. The study also finds that digital development has broadened the scope of service promotion through websites, social media, and electronic word of mouth. Therefore, the effectiveness of service promotion depends on the firm's ability to integrate promotional messages consistently, build customer trust, and deliver satisfying service experiences. Effective service promotion not only attracts market attention but also strengthens customer satisfaction and long term loyalty.